2002
DOI: 10.1080/01902140290096782
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pulmonary Toxicity of Various Soluble Metals Found in Urban Particulate Dusts

Abstract: The potential toxicity of an atmospheric dust sample EHC-93 has been attributed to the soluble fraction and, more specifically, to the zinc component. The concentration of Zn is the highest among the metals present in the soluble EHC-93 fraction. We now determine whether other metal components of this dust could cause similar lung injury if present at the same concentration as Zn (4.8 mg/g dust). Solutions of Zn, Cu, V, Ni, Fe, and Pb salts in 0.1 mL water were instilled to mouse lung and animals were killed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 20 publications
3
54
0
5
Order By: Relevance
“…Although some metals are essential for normal physiological function, excessive environmental exposure can be toxic (16,17). For instance, particulate matter and airborne particles containing high amounts of transitional metals, including zinc and copper, contribute to pulmonary and cardiovascular toxicity (18,19). Although recent studies have suggested that ion channels are potential molecular targets of transition metals (20), the mechanisms that confer the harmful effects of heavy metals are poorly understood.…”
Section: Znmentioning
confidence: 99%
“…Although some metals are essential for normal physiological function, excessive environmental exposure can be toxic (16,17). For instance, particulate matter and airborne particles containing high amounts of transitional metals, including zinc and copper, contribute to pulmonary and cardiovascular toxicity (18,19). Although recent studies have suggested that ion channels are potential molecular targets of transition metals (20), the mechanisms that confer the harmful effects of heavy metals are poorly understood.…”
Section: Znmentioning
confidence: 99%
“…The chemical composition of PM and particle size distributions are the most significant factors affecting air quality. In particular, the exposure to finer particles can cause short and long-term effects such as increased respiratory symptoms, decreased lung function, alterations in tissue and structure lung, in respiratory tract and premature death (Prieditis et al, 2002, Damek-Poprawa, 2003, Wahab et al, 2004, Huang and Ghio, 2006, Ahumada et al, 2007, Huang et al, 2007, Magas et al, 2007, Wild et al, 2009, Liuzzi et al, 2011. Moreover, near industrial areas, where elements and Polycyclic Aromatic Hydrocarbons (PAHs) are strongly associated with fine particles, increased toxicity and PM carcinogenicity have been determined (Bruno et al, 2002;Caselli et al, 2003;Pozzoli et al, 2004;Vione et al, 2004;Dvorsk脿 et al, 2011;Castro-Jim茅nez et al, 2012;Tobiszewski and Namiesnik, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Los isoprostanos son considerados marcadores biol贸gicos de estr茅s oxidativo, ya que se acumulan en estas condiciones 30 . El Cu +2 puede producir, por la reacci贸n de Fenton, especies reactivas de ox铆geno, que catalizan la formaci贸n de radicales hidroxilos a partir de per贸xido de hidr贸geno 6 . Adem谩s, puede participar en la reacci贸n de Haber-Weiss, catalizando la formaci贸n de radicales hidroxilos a partir de per贸xido de hidr贸geno y ani贸n super贸xido 31,32 .…”
Section: Discussionunclassified
“…La instilaci贸n intratraqueal de igual concentraci贸n de distintos metales (4,8 碌g de metal en 0,1 mL de agua) a ratas Spargue-Dawley detect贸 48 h post-instilaci贸n que zinc y cobre inducen aumento de macr贸fagos alveolares y de leucocitos polimorfonucleares y de la concentraci贸n de prote铆nas en el lavado broncoalveolar, mientras que otros metales como vanadio, n铆quel, hierro y plomo, no provocaron cambios significativos [5][6][7][8] .…”
unclassified